IMPLEMENTATION OF DIGITAL-BASED MARKETING IN CREATING SUSTAINABLE BUSINESS THROUGH SOSTAC ANALYSIS - Yudiandri, Tri Eko; Fitriana, Fitriana; Buchori, Apit; Sulistyo, Agung (Universitas Nusa Cendana, 2025)
This study aims to investigate innovations in digital-based marketing strategies in small and medium businesses. This study uses a qualitative research design. The object of this study is YAD Blangkon, which has implemented technology in its business marketing activities. Moreover, the study highlights the added value of successful business management and a 25% increase in sales value over the previous year. Various concepts can aid in the development of the managed business. One of the references and methods available is SOSTAC analysis. We chose this framework due to its conceptual nature, which enables the development of a more comprehensive digital-based business management strategy. Through a combination of interview activities and the application of the SOSTAC-RACE planning concept, this study produced findings on the application of digital-based business management strategies. This study shows the need for business actors to take various steps, including analyzing the business environment, conducting SMART analyses correctly, developing business strategies, and refining them through the application of tactics in the field.. Keywords: Tourism; Business; Sustainability, SOSTAC-RACE Planning